The chemical composition of a cold-pressed milk thistle seed flour extract, and its potential health beneficial properties. Issue 5 (12th April 2019) - Choe, Uyory; Li, Yanfang; Gao, Boyan; Yu, Lu; Wang, Thomas T. Y.; Sun, Jianghao; Chen, Pei; Yu, Liangli (Lucy)
Abstract : The chemical composition of a milk thistle seed flour extract and its potential health-promoting properties. Abstract : Cold-pressed milk thistle seed flour was extracted with 50% acetone and evaluated for its phytochemical composition, and gut microbiota modulating, free radical scavenging, anti-inflammatory and anti-proliferative capacities. UHPLC-MS analysis detected fifteen compounds in the milk thistle seed flour extract with silychristin as the primary component followed by silybin B and isosilybins A & B. The milk thistle seed flour extract enhanced the total bacteria number and altered the abundance of a specific bacterial phylum or genus under the experimental conditions. The extract had RDSC, ORAC, HOSC, and ABTS˙ + scavenging capacities of 49, 634, 10 420 and 116 μmol Trolox equivalents (TE) per g flour, respectively. In addition, the milk thistle seed flour extract suppressed LPS induced IL-1β mRNA expression in the cultured J774A.1 mouse macrophages and the proliferation of LNCaP prostate cancer cells. The results suggest milk thistle seed flour's potential health benefits in functional foods.